Diseño y construcción de una silla bipedestadora para personas con movilidad restringida grado IV en las extremidades inferiores con una capacidad de carga de 100 kg - Barbero Palacios, Jhonny Israel (2015)
This project is focused on the on the design and construction of a stand up wheelchair with load capacity of 100 kg to people with restricted mobility grade IV in the lower limbs. The majority of stand up wheelchair that exist in the country are from Argentina, Brazil, Chile, United Estates and Spain among others. However, the dimensions with which have been manufactured correspond to anthropometric measures of people of such countries. Therefore it is desirable to develop a chair in relation to the Ecuadorian people that cover the needs of the patients like comfort, security and consequently improve the activities of daily living. The first chapter deals with the theory of the wheelchairs, main parts, and classification. The second chapter consists of the design alternative with the respective matrix of weighting that presents six items: operation facility, muscular force, maintenance, installation, cost and materials, these will help to select the best option. The third chapter considers the design, selection of materials and solve of the components of the structure with the respective technical justification. The fourth chapter presents the costs and the process of construction of the stand up wheel chair. Finally the conclusion and recommendations are presented.